Factors Affecting Company’s Profitability: A Case Study of Company Financing under Mega And SBY Era - Sukirno Sukirno (Jurnal Akuntansi dan Bisnis, 2010)
This research is intended to show another proxy of government performance measurement from the capital market data. This research also is directed to compare the differences of company financing between Mega and SBY era, to examine the relationship of company financing and company profitability, and to interpret profoundly the results using the capital market data. Data were gathered from the Indonesian Capital Market Directory (ICMD) starting from 2001 up to 2006. Geometric mean was used to profoundly trace the influence of presidential leadership era and to balance financial data between Mega (2001 – 2003) and SBY era (2005). Hypotheses were confirmed by employing paired sample t test and linear regression analysis. This research draws three main conclusions. Firstly, collateral ratio and equity to total assets ratio are significantly different between Mega era and SBY era. Nevertheless, there is no significant difference in current liabilities to total assets, long-term liabilities to total assets, capital structure, and return on assets between Mega and SBY era. Secondly, current liabilities to total assets and long-term liabilities to total assets have a negative and significance influence to company’s profitability. Lastly, equity to total assets has a positive and significant effect on company’s profit. Findings are discussed to provide possibility factors behind the financing issue.